Sudden cardiac death and kidney health related problems among Nepali migrant workers in Malaysia - Aryal, Nirmal; Regmi, Pramod R; Faller, Erwin Martinez; Teijlingen, Edwin van; Khoon, Chan Chee; Pereira, Adrian; Simkhada, Padam (Nepal Journal of Epidemiology, 2019)
This paper reports on a consultation meeting that discussed two emerging health issues of Nepali migrant workers in Malaysia and the ways they can be addressed. Primarily, it focused on the issue of sudden cardiac deaths of Nepali migrant workers in Malaysia. This issue has been raised internationally by both scientific and media in the recent years. Secondly, it discussed kidney health related problem among Nepali migrant workers which has caught the attention of Nepali media recently. The meeting was organized in Kuala Lumpur, Malaysia on 19th April, 2019 where twenty people including health researchers, representatives of migrant related national and international organizations, and Nepali migrant workers participated. The meeting concluded that three types of data collection are needed: (1) good record of deaths, if at possible proper post-mortems; (2) a verbal autopsy tool to help identify underlying causes ; and qualitative research into kidney related problems.